(untitled) (Desenvolvimento em Questão, 2025)
Mosaics of Protected Areas emerge as an approach to strengthen the management of protected areas in Brazil, aiming for more effective governance through the integration of territories. We present the case of the Mosaic of the Lower Rio Negro (MBRN), in Amazonas, to reflect on the challenges of integrated management in Conservation Units with resident populations. Through structured questionnaires applied in 115 traditional communities of eight MBRN protected areas in 2022, we characterized productive practices and access to community infrastructure items. Later, we tested the hypothesis that larger traditional communities with more community infrastructure items present more productive practices. We identified that practices such as agriculture, fishing, crafts, and extractivism were homogeneous throughout the territory, while tourism activities, natural resource management, and livestock were developed in specific territories. No protected area can be characterized as excellent in relation to access to infrastructure, highlighting the precariousness of services in the region. We found that access to community infrastructure items enables the development of more productive practices, regardless of the size of the community. The territory of the MBRN revealed great heterogeneity in access to community infrastructure and socio-productive systems, which hinders the implementation of integrated management strategies. We highlight the significant challenge of jointly managing the territory to guarantee the quality of life and preserve the Amazon socio-biodiversity.